Rancang Bangun Sistem Infromasi Jasa Pengiriman Barang Berbasis Web pada CV. Dua Daya Express - Aziz, Achmad Sony Syaiful; Wurijanto, Tutut; Oktaviani, Oktaviani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
CV Dua Daya Express is a delivery service company. It’s based in Gresik and delivers things to many areas in Jawa, Bali and Sumatra. The company holds many transactions every month. And by that, the company sends many stuffs to customers by land. Despite of highly activities, CV Dua Daya Express only has two 2-tons-trucks. The company cooperates with another company to support the armada. They make a phone call and specifically give an information about what they currently need to deliver customer’s order. This system doesn’t have an efficiency and takes big effort from the staff. CV Dua Daya Express needs a new system for the effectiveness of delivery service.